Preventing Foodborne Illness: Campylobacteriosis - Soohyoun Ahn; Renée M. Goodrich-Schneider; Rachael Silverberg; Keith R. Schneider (EDIS, 2016)
Campylobacteriosis is a gastrointestinal infection caused by bacteria of the genus Campylobacter. These bacteria require low levels of oxygen to survive and have been found in wild birds, poultry, pigs, cattle, domesticated animals, unpasteurized milk, produce, and contaminated water. As part of a series on preventing foodborne illness, this revised 5-page fact sheet describes the Campylobacter bacteria, the causes and symptoms of campylobacteriosis disease, and how to prevent the disease through good sanitation methods and practices for receiving, handling, processing, and storing food products. Written by Soohyoun Ahn, Renée M. Goodrich-Schneider, Rachael Silverberg, and Keith R. Schneider, and published by the Food Science and Human Nutrition Department, December 2015.